Potentiometric and Chromatographic Study of Cu(II) and Al(III) Complexes of Quercetin - (:unkn) unknown (My University, 2017)
In this study, the stability constants of the copper(II) andaluminium(III) complexes of quercetin were determinedpotentiometrically by using Calvin-Bjerrum and Irwing Rossottimethods. The protonation constants of quercetin were found:logK 1 = 11.15±0.118, logK 2 = 10.42±0.144, logK 3 = 9.44±0.162,logK 4 = 8.28±0.151. For copper complex formation constantwas found by Irwing-Rossotti method: logK 1 = 19.92±0.367 andfor aluminium complex complex: logK 1 = 23.02±0.459. Fromthe results, the components of quercetin / metal complexes aregiven as 1/1 both copper(II) and aluminium(III).A reversed phase high pressure liquid chromatographic methodwas developed for the metal complexes which were preparedaccording to potentiometric results with the ratio quercetin /metal =1/1. Mobile phase was 0.01 M HClO 4 / 8.33 x 10 -5 Mquercetin in Methanol (40/60), column was XTerra RP18, 5 μm,4.6 x 150 mm , detector was Diode Array Detector at λ = 373 ve421 nm (band width 4nm).